The Basilar Artery on Computed Tomography Angiography Prognostic Score for Basilar Artery Occlusion. Issue 3 (March 2017) - Alemseged, Fana; Shah, Darshan G.; Diomedi, Marina; Sallustio, Fabrizio; Bivard, Andrew; Sharma, Gagan; Mitchell, Peter J.; Dowling, Richard J.; Bush, Steven; Yan, Bernard; Caltagirone, Carlo; Floris, Roberto; et al.
Abstract : Background and Purpose—: Basilar artery occlusion is associated with high risk of disability and mortality. This study aimed to assess the prognostic value of a new radiological score: the Basilar Artery on Computed Tomography Angiography (BATMAN) score. Methods—: A retrospective analysis of consecutive stroke patients with basilar artery occlusion diagnosed on computed tomographic angiography was performed. BATMAN score is a 10-point computed tomographic angiography–based grading system which incorporates thrombus burden and the presence of collaterals. Reliability was assessed with intraclass coefficient correlation. Good outcome was defined as modified Rankin Scale score of ⩽3 at 3 months and successful reperfusion as thrombolysis in cerebral infarction 2b-3. BATMAN score was externally validated and compared with the Posterior Circulation Collateral score. Results—: The derivation cohort included 83 patients with 41 in the validation cohort. In receiver operating characteristic (ROC) analysis, BATMAN score had an area under receiver operating characteristic curve of 0.81 (95% confidence interval [CI], 0.7–0.9) in derivation cohort and an area under receiver operating characteristic curve of 0.74 (95% CI, 0.6–0.9) in validation cohort. In logistic regression adjusted for age and clinical severity, BATMAN score of <7 was associated with poor outcome in derivation cohort (odds ratio, 5.5; 95% CI, 1.4–21; P =0.01), in validation cohort (odds ratio, 6.9; 95% CI, 1.4–33; P =0.01), and in endovascular patients, after adjustment for recanalization and time to treatment (odds ratio, 4.8; 95% CI, 1.2–18; P =0.01). BATMAN score of <7 was not associated with recanalization. Interrater agreement was substantial (intraclass coefficient correlation, 0.85; 95% CI, 0.8–0.9). BATMAN score had greater accuracy compared with Posterior Circulation Collateral score ( P =0.04). Conclusions—: The addition of collateral quality to clot burden in BATMAN score seems to improve prognostic accuracy in basilar artery occlusion patients. Abstract : Supplemental Digital Content is available in the text.